Determinants of health insurance ownership in Jordan: a cross-sectional study of population and family health survey 2017–2018 - Ruoxi Wang; Shangfeng Tang; Bishwajit Ghose; Meilian Liu; Zhaoxin Luo; Donghua Zhou; Lu Ji; Huilin Zhang (BMJ Open)
Objectives With about one-third of the population living below the poverty line, Jordan faces major healthcare, social and national development issues. Low insurance coverage among the poor and high out-of-pocket expenditure worsens the financial insecurity especially for the marginalised population. The Government of Jordan aims to achieve universal coverage of health insurance—a bold plan that requires research evidence for successful implementation. In this study, we aimed to assess the proportion of the population covered by any health insurance, and the determinants owing a health insurance.Design A population-based prospective cohort study.Setting Jordan.Methods Data for this study were derived from the Jordan Population and Family Health Survey, which was implemented by the Department of Statistics from early October 2017 to January 2018. Sample characteristics were described as percentages with 95% CIs. Binary logistic regression models were used to estimate OR of health insurance ownership. Parsimonious model was employed to assess the sex and geographical differences.Results Data revealed that in 2017–2018, 73.13% of the 12 992 men and women had health insurance. There was no indication of age of sex difference in health insurance ownership; however, marital status and socioeconomic factors such as wealth and education as well as internet access and geographical location appeared to be the important predictors of non-use of health insurance. The associations differed by sex and urbanicity for certain variables. Addressing these inequities may help achieve universal coverage in health insurance ownership in the population.Conclusions More than one-quarter of the population in Jordan were not insured. Efforts to decrease disparities in insurance coverage should focus on minimising socioeconomic and geographical disparities to promote equity in terms of healthcare services.